Testing the Role of Contextual Deliberation in the Compromise Effect - Guo, Liang (Management Science, 2022)
Many phenomena of preference construction demonstrate a violation of the rationality premise in classical economic theories. One of the most well-known examples of preference construction is the compromise effect. This puzzling anomaly can be rationalized by contextual deliberation (i.e., endogenous information retrieval/acquisition that can partially resolve utility uncertainty before choice). In this research, we investigate the empirical validity of this explanation by performing falsification tests for its necessary predictions and identifying it from other potential accounts. We conduct five experiments with more than 1,000 participants and show that the compromise effect can be positively mediated by response time and cannot be eliminated by context information, but it can be moderated by manipulating the level of deliberation (i.e., time constraint, preference articulation, task order). These findings are consistent with the predictions of the theory of contextual deliberation. We also show that, on average, contextual deliberation (as proxied by response time) can uniquely account for about half of the total compromise effect. This paper was accepted by Yan Chen, behavioral economics and decision analysis.